The Effects of Interaction between Climate Change and Land‐Use/Cover Change on Biodiversity‐Related Ecosystem Services - He, Xinyue (Glob Chall, 2019)
Climate change and land‐use/cover change (LUCC) are two major types of global environmental change. They are increasingly challenging the main objectives of ecosystem management, which are to provide ecosystem services sustainably to society and maintain biodiversity. However, a comprehensive understanding of how climate–land‐use change affects these primary goals of ecosystem management is still lacking. Here, a global literature review on the impacts of climate change and LUCC on ecosystem services related to biodiversity is presented. In this review, possible ecological responses at species, community, and ecosystem levels, and the effects of interaction mechanisms between climate change and LUCC on biodiversity‐related ecosystem services are identified. The results show possible effects on species facing climate change challenges through affecting distribution/range shifts, interspecific relations, richness, and abundance, and the impacts on biodiversity through increasing extinction rates, nutrient deposition, and habitat fragmentation under LUCC. Climate change may hinder the ability of species to deal with LUCC, and in turn LUCC could reduce resilience to climate change. Understanding of these interactions is necessary to address the increasing pressure on sustainable provisioning of ecosystem services under different climate and land‐use scenarios in the future.